2013
DOI: 10.1371/journal.pone.0070729
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Angiostrongylus cantonensis (Nematoda: Angiostrongylidae) Infections in Invasive Rodents from Five Islands of the Ogasawara Archipelago, Japan

Abstract: Background Angiostrongylus cantonensis (Chen, 1935) is a parasite of murid rodents and causative agent of human neuro-angiostrongyliasis. In 2011, the Ogasawara Islands in the western North Pacific were assigned a World Natural Heritage site status. The occurrence of A. cantonensis is well documented in the Chichijima, Hahajima, and Anijima Islands. However, the occurrence of A. cantonensis in the other islands of the Ogasawara Islands has not been reported.Methodology/Principal FindingsBetween March 2010 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…We speculate that the rapid spread of A. cantonensis in the Pacific region was a consequence of naval operations during and/or after the World War II, because troop and supply ships could readily permit spread of the A. cantonensis infected rats and/or snails. In a telling analogy, A. cantonensis repeatedly colonised Japan during the 20th century, spreading from southern islands to the north resulting in a presence of several different haplotypes from three clades [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that the rapid spread of A. cantonensis in the Pacific region was a consequence of naval operations during and/or after the World War II, because troop and supply ships could readily permit spread of the A. cantonensis infected rats and/or snails. In a telling analogy, A. cantonensis repeatedly colonised Japan during the 20th century, spreading from southern islands to the north resulting in a presence of several different haplotypes from three clades [22].…”
Section: Discussionmentioning
confidence: 99%
“…Southeast Asia (including China, Taiwan, Vietnam, Thailand, Laos, Cambodia and Myanmar) is considered to be the original endemic region for A. cantonensis [21, 22, 2735]. In Japan, Tokiwa et al [33] suggested colonization of the area by multiple genetic lineages spreading from the south to the north of Japan.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ribosomal DNA sequences were used to assess metastrongylid nematode relationships (Carreno & Nadler, 2003) or to help survey larvae from mollusk intermediate hosts (Fontanilla & Wade, 2008; Qvarnstrom, Sullivan, Bishop, Hollingsworth, & da Silva, 2007; Qvarnstrom et al., 2010), and ~360‐bp region of the cytochrome c oxidase 1 ( CO 1) gene was used to assess relationships to other species of Angiostrongylus (Eamsobhana et al., 2010). To date, molecular systematic/phylogeographic studies on A. cantonensis have mainly used two mitochondrial (mtDNA) markers, CO 1 and cytochrome b ( CYTB ), where the focus has largely been descriptive in terms of reporting local patterns of haplotype variants (Aghazadeh et al., 2015; Dalton, Fenton, Cleveland, Elsmo, & Yabsley, 2017; Dusitsittipon, Criscione, Morand, Komalamisra, & Thaenkham, 2017; Dusitsittipon, Thaenkham, Watthanakulpanich, Adisakwattana, & Komalamisra, 2015; Eamsobhana, Song, et al., 2017; Eamsobhana, Yong, et al., 2017; Lv et al., 2012; Monte et al., 2012; Moreira et al., 2013; Nakaya et al., 2013; Okano et al., 2014; Rodpai et al., 2016; Simoes et al., 2011; Tokiwa et al., 2012, 2013; Vitta et al., 2016; Yong, Eamsobhana, Song, Prasartvit, & Lim, 2015; Yong, Song, Eamsobhana, Goh, & Lim, 2015; Yong, Song, Eamsobhana, & Lim, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…One of the theories for the appearance of this nematode outside of Southeast Asia is that its spread has been facilitated by the introduction of the giant African snail, Achatina fulica, which could have carried the parasite across the Pacific where rat populations were already established [21][22][23]. Hochberg et al (2007) [24] proposed that the spread of A. cantonensis has been driven by climate change factors and globalization, as well as by the increasing international trade.…”
Section: Introductionmentioning
confidence: 99%